Information security for managers - Workman, Michael D. 1957-; Gathegi, John N.; Phelps, Daniel C. (Burlington, Massachusetts : Jones & Bartlett Learning, 2013)
Information systems have improved over the years to become more effective in collecting and rendering information for consumers, although these improvements have been accompanied by increases in both frequency and sophistication of attacks against them. The impacts from attacks against companies are significant, and managers are responsible for their organizations' security. Failures can cause significant losses to companies and their suppliers and clients, and may cost managers their jobs, and may even possibly lead to legal liabilities that are adjudicated against them. This textbook takes a different approach than most texts on the subject, which are organized topically. Pedagogically, Information Security for Managers utilizes an incremental development method called knowledge scaffolding -- a proven educational technique for learning subject matter thoroughly by reinforced learning through an elaborative rehearsal process. This new resource includes coverage on threats to confidentiality, integrity, and availability, as well as countermeasures to preserve these. The textbook also draws extensively from the latest applied research and development, rather than simply rehashing materials and topics that are in nearly all of the extant textbooks and popular reading materials
1. What should managers know about security policies and procedures? -- 2. Technology orientation for managers -- 3. Computer and network security -- 4. Managing organizations securely
Includes bibliographical references and index
Keywords: Business enterprises -- Security measures; Computer networks -- Security measures; Computer security -- Management; Information technology -- Security measures